Country profile : Romania - Economist Intelligence Unit (Great Britain) (Economist Intelligence Unit, 1968)
"Annual survey of political and economic background".Continues in part: Quarterly economic review of Rumania, Bulgaria, Albania, ISSN 0142-4068.